Strategi Pengembangan Motivasi Instrinsik Di Dalam Pembelajaran Siswa Sekolah Dasar - Laesti Nurishlah; Mohamad Yudiyanto; Anisa Nurlaila; Mangun Rusnaya (MURABBI, 2023)
This research highlights the importance of understanding the role of intrinsic motivation in student learning along with various strategies for developing approaches to enhance intrinsic motivation in elementary schools. By designing a learning environment that stimulates students' intrinsic interest and understanding the complexity of the interaction between intrinsic and extrinsic motivation, teachers can assist students in reaching their full potential in learning. Thus, a profound understanding of intrinsic motivation is not only a necessity for students and teachers but also a key to creating meaningful and satisfying learning experiences for elementary school students. Penelitian ini menyoroti pentingnya memahami peran motivasi instrinsik dalam pembelajaran siswa beserta ragam strategi pengembangan strategi untuk meningkatkan motivasi intrinsik di Sekolah Dasar. Dengan merancang lingkungan pembelajaran yang menggugah minat intrinsik siswa dan memahami kompleksitas interaksi antara motivasi intrinsik dan ekstrinsik, guru dapat membantu siswa mencapai potensi penuh mereka dalam pembelajaran. Dengan demikian, pemahaman yang mendalam tentang motivasi instrinsik bukan sekedar kebutuhan bagi siswa dan guru, tetapi juga merupakan kunci dalam menciptakan pengalaman pembelajaran yang bermakna dan memuaskan bagi siswa sekolah dasar.